Teacher resources in veterinary medicine in Colombia - Hernández Vásquez, Aureliano (Universidad de La Salle. Revistas. Revista de Medicina Veterinaria., 2016)
With the aim of gathering information on the human capital dedicated to teaching in programs of veterinary medicine (VM) and their postgraduate training in Colombia, the study analyzes eleven programs of VM and veterinary medicine and zootechnics (VMZ), including the longest running ones in the country, and 90 % of the accredited programs. Out of a total of 175 professors, 17.14 % have a PhD degree; 8.74 % are professional doctors; and 37.71% have a MSc degree. 17.14 % of the teachers are in the rank of specialist or professional expert. 19.42 % do not have a graduate degree. Most of the doctors are concentrated in three universities. There is a greater number of professors with professional graduate studies in clinical issues, while in the basic cycle there is a greater proportion of teachers with PhD degrees. Given the shortage of teachers with advanced academic degrees, the clear oversupply of graduates in VM and VMZ regarding demand, and the scarcity of plans for teacher specialization, it is desirable to restrain the opening of new programs. This study can help to project plans for human talent development in programs of VM and VMZ in Colombian institutions.